Fabricação e caracterização de dispositivos baseados em nanofitas de Óxido de Estanho (SnO2) - Araujo, Luana Santos (Universidade Federal de São Carlos, 2012)
The structural and transport features of tin oxide nanobelts synthesized by the vapor-solid method combined with the carbothermal reduction process were investigated in this work. The samples synthesized were characterized by using experimental techniques such as scanning and transmission electron microscopy and x-ray diffraction. The nanobelts were found to be single crystals of rutile-type structure with a well defined growth direction. Electronic devices based on single nanobelt and on nanobelts dispersion were fabricated to measure the electronic properties of these samples. The semiconductor behavior was observed by the electron transport measurements data performed on a single nanobelt device, which pointed to the variable range hopping process as the main transport mechanism in a large range of temperature (77 K <T <250 K). The characteristics and the charging processes at the interface between metal and semiconductor were used as a basic tool in the investigation of conduction mechanisms. Experimental curves obtained from nanobelts dispersion devices were described by a model based on the thermionic emission theory. The model allowed the analysis of different Schottky barriers on the same device and allowed the study of barrier dependence on the metal work function and the existence of interface states. The experimental values of the Schottky barriers showed independence with the metal work function metal used but a very high correlation with the Bardeen model. This result is a consequence of the presence of interface states that induce Fermi level to show a fixed value around the charge neutral level resulting in the independence between the Schottky barriers and the metal contacts.
Keywords: Física da matéria condensada; Dióxido de estanho; Nanofitas; Transporte eletrônico; CIENCIAS EXATAS E DA TERRA::FISICA